Perbedaan Keterampilan Berpikir Kritis Siswa yang Berbantuan Media Audio Visual dan LKS Cetak Sebagai Panduan Percobaan pada Metode Eksperimen dengan Pendekatan Verifikasi Kelas XI Semester 2 SMA Negeri 1 Sewon - suryandari suryandari (Tarbiyah : Jurnal Ilmiah Kependidikan, 2018)
This research purposed to know the differences of student cognitive critical thinking and psychomotor skills, along with knowing where was the better group between audio visual media and paper sheet in  student cognitive critical thinking and psychomotor skills as experiment guidelines . Critical thinking skills that analyzed were belonged to  priority, analyzed, synthesis, and evaluation aspects.This research was an quasi-experiment with the static pretest posttest group design. The populate was belonged to all student of XI IPA 1, XI IPA 3, and XI IPA 5. The sample was  given by cluster random sampling, and the result is XI IPA 1 as the group help by audio visual media, XI IPA 5 as paper sheet. The instruments  were  10 questions of critical thinking skill and psychomotor observation  sheet. Data were obtained  from posttest and psychomotor observation  scores. Data analyzing used independent sample T-test and different populate average estimation test.The results showed that there were differences of  student  cognitive critical thinking and psychomotor skills between of  the group that helped by audio visual media and paper sheet, along with the student cognitive critical thinking and psychomotor skills of audio visual media group are better than paper sheet, it was  because of the ranges of  different average populate estimation in cognitive aspect  was ranging from 0,1246 9,2313 and psychomotor was 7,752 12,906   for each α = 5%